FEATURES OF ACCOUNTING EQUITY CAPITAL COMPONENTS - Sherimbetov Inomjon Xalilullayevich (Research Parks Publishers, 2023)
Equity capital is of great importance in ensuring the financial stability of commercial organizations. In particular, reserve and retained earnings, which are a component of equity capital, reflect the result of the company's financial and economic activities. The growth of equity capital indicates the efficiency of the company. Of course, in this case, the interests of the company's shareholders and creditors will be protected by their correct accounting. The article describes the features of accounting for reserve capital and retained earnings based on national and international standards